CODE SWITCHING AND MIXING IN SOCIAL INTERACTIONS BETWEEN STUDENTS - Nurlela Majrul; Siti Meutia Sari; Erikson Saragih; Khairina Nasution (Rahis Cendekia Indonesia, 2024)
This research is qualitative research, namely by providing a systematic and accurate description of code switching and mixing in social interactions among students on the Graha Nusantara University Padangsidimpuan campus. we can find that the interactions carried out by students on campus actually involve code switching, this is due to the mastery of more than one language and then the speaker, listener, the presence of a third person, informal conversations used in the campus area. And what causes code mixing to occur is the use of popular terms such as the phrase